Quantifying uncertainties in the sustainability evaluation of concrete materials considering regional characteristics in Japan - Nicole Alexis Kwan Vios; Michael Ward Henry; Joel Galupo Opon (Acta Polytechnica CTU Proceedings)
In the evaluation of concrete sustainability, what constitutes "sustainable" to one region may vary from another. This often leads to methodological forms of uncertainties that makes the evaluation process more complex. As such, this paper aims to quantify the effect of uncertainties in the regional context on the sustainability evaluation of concrete materials. This is carried out by quantifying the regional context through establishing a weighting scheme and then integrating the obtained weights into the sustainability analysis of concrete materials in tandem with uncertainty analysis. Japan is used as a case study because although it relatively appears as a homogeneous country, its prefectures possess unique characteristics that may make the sustainability evaluation of concrete materials vary across prefectures. Cluster analysis is carried out in the 47 prefectures of Japan using a set of regional context indicators. Five clusters are identified with varying characteristics and these are translated into different weighting schemes. The established weights are used in the sustainability evaluation of concrete materials using multi-criteria decision-making analysis. The results showed that one mix is the most sustainable for four of the clusters and a different mix is the most sustainable for the remaining cluster. When uncertainty analysis is conducted, the effect of the weights in the sustainability evaluation is explained by examining the average scores of the concrete mixes and the variance of the scores across the five clusters. This investigation facilitated the understanding of how regional differences and the uncertainties associated with it impact the evaluation of concrete sustainability.